The rules of matrimony - Walker, Anneka R. (Walker, Anneka R. Matchmaking mamas series, 2025)
"Lord Ian Reynolds, determined to avoid marriage after his father's betrayal, becomes entangled in a fake engagement with Miss Amie Tyler. Forced into a calculated union, Ian, with his political ambitions, and Amie, with her desire for independence, clash. Yet their affection grows. As love blossoms, they must decide whether risking their independence is worth pursuing a future together"--